2019
DOI: 10.1016/j.ijar.2018.12.014
|View full text |Cite
|
Sign up to set email alerts
|

A capacity-based framework encompassing Belnap–Dunn logic for reasoning about multisource information

Abstract: Open Archive Toulouse Archive OuverteOATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible A capacity-based framework encompassing Belnap-Dunn logic for reasoning about multisource information ✩,✩✩ a b s t r a c t Keywords: Belnap-Dunn logic Inconsistency handling Kleene and Priest logics Capacities Possibility theory Modal logicBelnap-Dunn four-valued logic is one of the best known logics for handling elementary information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Theorem 1. γ is separable if and only if γ = ⊗E∈Fγ N E . 12 This result strikingly differs from the case of numerical separable belief functions, whose focal sets do not satisfy Eq. ( 17), but are closed under conjunction [67].…”
Section: So We Have Shown the Following Resultmentioning
confidence: 65%
See 1 more Smart Citation
“…Theorem 1. γ is separable if and only if γ = ⊗E∈Fγ N E . 12 This result strikingly differs from the case of numerical separable belief functions, whose focal sets do not satisfy Eq. ( 17), but are closed under conjunction [67].…”
Section: So We Have Shown the Following Resultmentioning
confidence: 65%
“…In [12], it is shown that Belnap logic can be encoded in a simplified modal logic where modalities are interpreted by means of Boolean capacities.…”
Section: Dempsterian Qualitative Specialisationmentioning
confidence: 99%